Psychological Well-Being In People With Chronic Diseases - Azfaruddin, Muhammad Farid; Rini, Afinia Sandhya (Academic Journal of Psychology and Counseling, 2023)
Physical, psychological and spiritual problems are often faced by patients suffering from increasingly severe chronic diseases. This research focused on the psychological well-being of people with long-term chronic diseases. This qualitative research employed a case study approach. It involved three informants who had experienced or were suffering from chronic diseases for more than one year. The results revealed several important themes, namely, the need to meet the psychological needs of people suffering from chronic diseases. In addition, this study found that self-acceptance and social support were the most important factors for improving the mental health of people with chronic diseases.